La città leggera: Smart City e urbanistica attuativa The lightweight city: Smart city and operative planning - Giuseppe Mazzeo (Smart City, Urban Planning for a Sustainable Future, 2016)
Cities are in a state in which two opposing forces are acting on them: on the one hand the unabated urbanization process, on the other the evergrowing demand for real sustainability. The book proposes an urban planning response focused on the transformations of urban sectors to be achieved using innovative operative tools; for this aim the book defines the main features of this operative tools. The goal is to include in the cities innovative actions that can provoke a domino effect with repercussions on the entire urban structure. The book is devided in 5 sections. The first one addresses the issue of urbanization and the development of the urban systems, with the related implications in terms of resource consumption and concentration of people and functions. The second part discusses some models that explain the mechanisms of urban sprawl and the derived scenarios. The third part deals with one of the key nodes of the relationship between urban systems and environmental resources, namely the energy. The fourth part analyzes some international case studies to extrapolate recurring characteristics that can affect the operative planning. The fifth section focuses on the features of this new type of plan.